Aplikasi Timeline dalam Proses Pembangunan Konstruksi Booth Pameran pada Event Maker Fest 2018 - Ulfa Arin Rochmawati; Maswir Maswir (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
In the construction of Exhibition Booth appropriate management is needed, 9the things that need to be considered are regarding the quality of construction, costs and time that must be arranged in such a way as to obtain optimal results in accordance with client specifications for the success of an event. This study discusses how the development of Exhibition Booth using the production timeline with proven results as a reference in monitoring the loading process at the Event Tokopedia Maker Fest 2018. The data analysis method used in this study is descriptive analysis where the writer will describe the process starts from marking until all the components on the event booth perfectly.